Nilai Didaktis Folklor “Lutung Kasarung” Karya Ki Raksa Sunda - Edi Sukmara; Idan Setiari (Jurnal Soshum Insentif, 2019)
This study examines the subject of folklore "Lutung Kasarung" by Ki Raksa Sunda. The purpose of this study is to describe the didactic values contained in the folklore. The descriptive method used is to describe the level of didactic values in accordance with the educational criteria. The result of research that the most dominant didactic value in folklore "Lutung Kasarung" is the value of personality development (love, tolerance), humanity and society (please-help, obedience or obedience, conference), and religious values (faith, greed, character).